Case Report: Dual-Energy Computed Tomography of Cardiac Changes in IgG4-Related Disease - Wang, Ying; Zhou, Hui; Hu, Ping; Zhao, Jie; Mao, Yitao; Li, Zhixiao; Zhao, Xi (Frontiers in Cardiovascular Medicine, 2022)
Background Dual-energy computed tomography (DECT) is used in coronary plaque characterization, myocardial perfusion imaging, and pulmonary embolism diagnosis; however, there is no relevant research on DECT in IgG4-related diseases (IgG4-RD) involving the coronary artery. We are the first to report DECT findings of cardiac morphology and function in IgG4-RD. Patient Findings Multimodality cardiovascular imaging from a 63-year-old male patient, who presented with IgG4-related pancreatitis, was analyzed. An iodine map and spectral curves were obtained from the DECT, which can help to distinguish between non-calcified plaques and IgG4 lesions of the coronary artery, noninvasive FFRCT (fractional flow reserve derived from coronary computed tomography angiography) and ECV (extracellular volume fraction) demonstrated myocardial ischemia and myocardial fibrosis, respectively. Conclusion The DECT can detect coronary artery tumor-like lesions caused by IgG4-RD and simultaneously assess the morphological, functional, and histological characteristics of the myocardium. This may help to guide individualized and timely treatment and avoid potentially life-threatening complications.